2012
DOI: 10.1111/j.1439-0426.2012.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary arachidonic acid during the Artemia feeding period on larval growth and skeletogenesis in Senegalese sole, Solea senegalensis

Abstract: Summary To improve the understanding of the incidence of skeletal deformities in Senegalese sole (Solea senegalensis), a feeding trial was carried out to evaluate the effect of increasing dietary arachidonic acid (ARA) levels during the Artemia feeding period on larval growth and skeletogenesis. Larvae were fed from 8 to 50 days post hatching (dph) with Artemia nauplii enriched with three different levels of ARA: ARA‐Low, ARA‐Medium and ARA‐High (1.0, 4.5 and 7.0% ARA of total fatty acids, respectively). Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 46 publications
1
48
2
Order By: Relevance
“…This observation is in agreement with previous studies reporting the importance of ARA in Atlantic Salmon (Stubhaug et al, 2005;Tocher et al, 2000), the dietary inclusion of which, nevertheless, must be properly balanced with the inclusion of dietary EPA towards maximising performances in Atlantic Salmon diets. The results of this study complimented other teleost fish studies showing the positive effect of dietary ARA in fish (Atalah et al, 2011;Boglino et al, 2012;Luo et al, 2012;Xu et al, 2010) and contrary, other studies have shown that dietary ARA did not affect fish growth (Copeman et al, 2002;Fountoulaki et al, 2003;Koven et al, 2001). Based also on the results achieved in the present study, which D-ARA/EPA outperformed the other treatments, it seems possible that these discrepancies reported for growth related effects of dietary ARA may likely be related to the interaction with dietary EPA.…”
Section: Discussioncontrasting
confidence: 46%
“…This observation is in agreement with previous studies reporting the importance of ARA in Atlantic Salmon (Stubhaug et al, 2005;Tocher et al, 2000), the dietary inclusion of which, nevertheless, must be properly balanced with the inclusion of dietary EPA towards maximising performances in Atlantic Salmon diets. The results of this study complimented other teleost fish studies showing the positive effect of dietary ARA in fish (Atalah et al, 2011;Boglino et al, 2012;Luo et al, 2012;Xu et al, 2010) and contrary, other studies have shown that dietary ARA did not affect fish growth (Copeman et al, 2002;Fountoulaki et al, 2003;Koven et al, 2001). Based also on the results achieved in the present study, which D-ARA/EPA outperformed the other treatments, it seems possible that these discrepancies reported for growth related effects of dietary ARA may likely be related to the interaction with dietary EPA.…”
Section: Discussioncontrasting
confidence: 46%
“…Documented interannual variability of phytoplankton blooms in relation to thermal shifts could lead to asynchrony with the prey resources necessary for larval growth and development to metamorphosis (Mackas et al, 1998;Edwards and Richardson, 2004). Metamorphosis is an energetically demanding process and it is likely that larval fish must meet some energy storage requirement prior to initiating metamorphosis (Boglino et al, 2012;Fraboulet et al, 2010). Spatial and temporal mismatches with prey may have negative implications for larval growth as well as energy stores prior to metamorphosis .…”
Section: Introductionmentioning
confidence: 98%
“…To date, most studies dealing with the effect of dietary EFA levels on skeletogenesis in fish have focused their investigation on the role of DHA and EPA (Villeneuve et al., ; Kjørsvik et al., ; Roo et al., ; Dâmaso‐Rodrigues et al., ; Boglino et al., 2012a; Izquierdo et al., ), but only a few have focused on investigating the effects of ARA on bone during fish larval development (Boglino et al., 2012b, ). ARA is the major precursor for eicosanoids synthesis, enhancing the immune system and resistance to stress, among other important physiological processes (Bell and Sargent, ), and it directly competes with EPA for the enzymes involved in prostaglandin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%